Artificial intelligence in healthcare - N. M. Hettiarachchi; S. R. Manilgama; A. D. M. D. Liyanage (Sri Lanka College of Internal Medicine, 2023)
Artificial Intelligence (Al) has emerged as a transformative force in various fields, and its potential in medicine is particularly remarkable. The application of Al in healthcare holds immense promise, as it has the ability to revolutionise medical practice and the delivery of healthcare services. Over the past decade, Al has made significant strides in numerous medical specialties, presenting opportunities to enhance patient care, diagnostics, personalised treatment plans, and administrative processes within healthcare organisations. However, despite the tremendous opportunities presented by Al in medicine, there are also significant challenges to overcome.